2008
DOI: 10.1021/ja8068853
|View full text |Cite
|
Sign up to set email alerts
|

Photostable Single-Molecule Nanoparticle Optical Biosensors for Real-Time Sensing of Single Cytokine Molecules and Their Binding Reactions

Abstract: We synthesized tiny stable silver nanoparticles (2.6 ± 1.1 nm) and used its small surface area and functional groups to control single molecule detection (SMD) volumes on single nanoparticles. These new approaches allowed us to develop intrinsic single molecule nanoparticle optical biosensors (SMNOBS) for sensing and imaging of single human cytokine molecules, recombinant human tumor necrosis factor-α (TNFα), and probing its binding reaction with single monoclonal antibody (MAB) molecules in real-time. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
195
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(200 citation statements)
references
References 47 publications
(128 reference statements)
5
195
0
Order By: Relevance
“…Noble metals do not suffer some of the problems of photobleaching associated with fluorophores and blinking associated with quantum dots. The Xu research group at Old Dominion has described their major progress towards creating stable noble metal nanoparticles that have been called single molecule nanoparticle optical nanobiosensors (SMNOBS) that have been used for sensing TNF-α [243]. This work demonstrated the ability to track the on-off kinetics of TNF-α onto the Ag nanoparticles.…”
Section: Optical Methodsmentioning
confidence: 99%
“…Noble metals do not suffer some of the problems of photobleaching associated with fluorophores and blinking associated with quantum dots. The Xu research group at Old Dominion has described their major progress towards creating stable noble metal nanoparticles that have been called single molecule nanoparticle optical nanobiosensors (SMNOBS) that have been used for sensing TNF-α [243]. This work demonstrated the ability to track the on-off kinetics of TNF-α onto the Ag nanoparticles.…”
Section: Optical Methodsmentioning
confidence: 99%
“…The toxicity of the nanoparticles is discussed in [118]. In large amounts, however, their toxicity is high, and the biocompatibility is substantially lower than for gold nanoparticles [119][120][121][122].…”
Section: Bactericidal Characteristics Of Stabilized Silver Nanostructmentioning
confidence: 99%
“…5 In addition, Ag-NPs have been studied for industrial use in optics, sensors, imaging, and catalysis. [6][7][8][9][10] However, some studies have shown that Ag-NPs have adverse effects on mammalian cells. [11][12][13][14][15] It has been reported that the generation of reactive oxygen species (ROS) is one of causes of Ag-NP toxicity, because cells exposed to Ag-NPs show elevated ROS levels, lipid peroxidation, expression of oxidative stress responsive genes, and reduction of glutathione.…”
mentioning
confidence: 99%